2012
DOI: 10.1259/bjr/90024696
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation combined with transcatheter arterial embolisation in rabbit liver: investigation of the ablation zone according to the time interval between the two therapies

Abstract: Objectives: This study was designed to evaluate the extent of the radiofrequency ablation zone in relation to the time interval between transcatheter arterial embolisation (TAE) and radiofrequency ablation (RFA) and, ultimately, to determine the optimal strategy of combining these two therapies for hepatocellular carcinoma. Methods: 15 rabbits were evenly divided into three groups: Group A was treated with RFA alone; Group B was treated with TAE immediately followed by RFA; and Group C was treated with TAE fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…First, TACE and subsequent RFA was performed in a single session without time delay in this study, whereas RFA was performed one week after TACE in the previous one. An animal study investigating the ablation zone according to time interval between two treatments reported that a single-session combination could create a larger ablation zone than a dual-session combination (21). Thus, there might be a difference in LTP rates between single-session and dual-session combinations.…”
Section: Discussionmentioning
confidence: 99%
“…First, TACE and subsequent RFA was performed in a single session without time delay in this study, whereas RFA was performed one week after TACE in the previous one. An animal study investigating the ablation zone according to time interval between two treatments reported that a single-session combination could create a larger ablation zone than a dual-session combination (21). Thus, there might be a difference in LTP rates between single-session and dual-session combinations.…”
Section: Discussionmentioning
confidence: 99%
“…Although TACE seemed to have higher CR rate theoretically, most embolization agents remained in the tumor only for a few weeks [28] and led to reperfusion of the tumor which might be construed as CR immediately after embolization. Based on this reason, some authors suggested Transcatheter Arterial Embolization (TAE) or TACE should be followed by RFA as quickly as possible to create a larger ablation volume [29,30]. However, it was not practical to apply combined treatment with RFA and TACE in most clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] The sequential timing of administration may also be an influential factor, as TAE followed immediately by RFA in a single session showed a significantly larger volume of ablation than dual-session administration of TAE followed by RFA 5 days later (4.72 AE 2.61 vs. 2.43 AE 1.05 [p ¼ 0.008]). 19 In addition to the aforementioned synergism, tumor staining during TAE or TACE with ethiodized oil, retained iodinated contrast, or radiopaque beads enhances tumor conspicuity for improved targeting of treatment margins during thermal ablation. 20…”
Section: Combination Therapy Thermal Ablationmentioning
confidence: 99%